Psicologia do processo de decisão numa crise organizacional - Lisondo, Héctor Rafael (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper analyses the interaction of the psychological, technical, and administrative aspects which intervene in the dynamics of the decision-making process in a middle-sized Brazilian trading and product distribution company going through a crisis period. The systemic reality in which the relations between causes and effects are not evident and may be distant in time and in space and may induce an adverse emotional condition in the future of the organization. A diagnosis was obtained by means of the participating research process which also resulted in a technical and psychological help. This process has provided the leaders with an opportunity to bring awareness and to express the feelings and emotions resulting from the crisis, which, when repressed, affect the thinking process. It has also signaled the presence, in the everyday environment, of factors adverse to the reality criterion (and the possible consequences of their influence in the decision-making process). Finally, it has contributed to identify and build up a list of favorable alternatives to the efficacy of the decisions, so that the organization development could be retaken. The management can, this way, understand this new reality – as a discovery – which enabled to change a trend towards its decline, to prevent its possible dissolution and to retake its evolution. Keywords: Decision-making process; Leadership; Changes and resistences.